Rational Design, Synthesis, and Evaluation of Fluorescent CB2 Receptor Ligands for Live-Cell Imaging: A Comprehensive Review - Pinaki Bhattacharjee; Malliga R. Iyer (MDPI AG, 2023)
The cannabinoid receptors CB1 and CB2 are class A G protein-coupled receptors (GPCRs) that are activated via endogenous lipids called endocannabinoids. The endocannabinoid system (ECS) plays a critical role in the regulation of several physiological states and a wide range of diseases. In recent years, drug discovery approaches targeting the cannabinoid type 2 receptor (CB2R) have gained prominence. Particular attention has been given to selective agonists targeting the CB2 receptors to circumvent the neuropsychotropic side effects associated with CB1 receptors. The pharmacological modulation of CB2R holds therapeutic promise for various diseases, such as inflammatory disorders and immunological conditions, as well as pain management and cancer treatment. Recently, the utilization of fluorescent probes has emerged as a valuable technique for investigating the interactions between ligands and proteins at an exceptional level of spatial and temporal precision. In this review, we aim to examine the progress made in the development of fluorescent probes targeting CB2 receptors and highlight their significance in facilitating the successful clinical translation of CB2R-based therapies.